An order in Lewy body disorders: Retrograde degeneration in hyperbranching axons as a fundamental structural template accounting for focal/multifocal Lewy body disease. Issue 2 (14th November 2016) - Uchihara, Toshiki
Abstract : Initial clinical recognition of "paralysis agitans" by James Parkinson was expanded by Jean‐Martin Charcot, who recognized additional clinical findings of his own, such as slowness (distinct from paralysis), rigidity (distinct from spasticity) and characteristic countenance. Charcot assembled these findings under the umbrella of "Parkinson disease (PD)". This purely clinical concept was so prescient and penetrating that subsequent neuropathological and biochemical evidences were ordered along this axis to establish the nigra‐central trinity of PD (dopamine depletion, nigral lesion with Lewy bodies: LBs). Although dramatic efficacy of levodopa boosted an enthusiasm for this nigra‐centralism, extranigral lesions were identified, especially after identification of alpha‐synuclein (αS) as a major constituent of LBs. Frequent αS lesions in the lower brainstem with their presumed upward spread were coupled with the self‐propagating property of αS molecule, as a molecular template, to constitute the prion‐Braak hypothesis. This hybrid concept might expectedly explain clinical, structural and biochemical features of PD/dementia with Lewy bodies (DLB) as if they were stereotypic. In spite of this ordered explanation, recent studies have demonstrated unexpectedly that αS lesions in the human brain, as well as their corresponding clinical manifestations, are much more disordered. Even with such a chaos of LB disorders, affected neuronal groups are uniformly characterized by hyperbranching axons, which may facilitate distal‐dominant degeneration and retrograde progression of LB‐related degeneration along axons as a fundamental structural order to template LB disorders. This "structural template" hypothesis may explain why: (i) some selective groups are prone to develop Lewy pathology; (ii) their clinical manifestations (especially non‐motor components) are vague and generalized without somatotopic accentuation; (iii) distal axons and terminals are preferentially affected early, which is clinically detectable as reduced myocardial uptake of meta ‐iodobenzylguanidine in PD/DLB. Because each Lewy‐prone system develops LBs independently, their isolated presentation as "focal LB disease" or their whatever combinations as "multifocal LB disease" are a more plausible framework to explain clinicopathological diversities of LB disorders. Clinical criteria are now being revised to integrate these clinicopathological disorders of PD/DLB. To gain closer access to the reality of the human brain, it is necessary to facilitate more interactions between clinicopathological and experimental fields so that both are mutually critical and complementary for improved diagnosis and treatment.